Upacara Kematian Adat Masyarakat Karo Ditinjau Dari Aqidah Islam - Andika Ari Syahputra (UIN Sumatera Utara, 2021)
This article is to identify, analyze and conduct a study of the Death Ceremony in the Karo people's customs in terms of the Islamic Aqeedah, therefore this research is a qualitative descriptive research. Qualitative descriptive method is a research method based on the philosophy of postpositivism used to look at the natural condition of objects (as opposed to experiments) where the researcher is the key instrument of data collection techniques carried out by trigulation (combined), data analysis is inductive/qualitative, and qualitative research results emphasize meaning rather than generalization. The time used in this study was in September 2020, the research location was in Gunung Village, Kec. Tiga Binanga, Kab. Karo, to get definite data and information about